Effect of hyoscine butylbromide on prostate multiparametric MRI anatomical and functional image quality. Issue 2 (February 2018) - Slough, R.A.; Caglic, I.; Hansen, N.L.; Patterson, A.J.; Barrett, T.
Abstract : Aim: To evaluate the effect of the spasmolytic agent hyoscine butylbromide (HBB) on the quality of anatomical and functional imaging of the prostate. Materials and methods: One hundred and seventy-three patients were included in this retrospective study. Eighty-seven patients received intravenous HBB prior to scanning (HBB group) and 86 patients did not (non-HBB group). Multiparametric (mp) 3 T magnetic resonance imaging (MRI) was performed using a 32-channel body coil. Two radiologists independently evaluated the image quality of T2-weighted imaging (WI), diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) maps, using a five-point Likert scale. DWI was further assessed for distortion and artefact (four-point Likert scale), and T2WI for the presence of motion artefact or blurring. Dynamic contrast-enhanced (DCE) image quality was assessed by recording the number of corrupt contrast curve data points. Results: T2W image quality in the HBB group was significantly higher than in the non-HBB group (3.63±1.11 versus 2.84±0.899); p< 0.001. The HBB group also showed significantly less T2W motion and T2W blur than the non-HBB group (23% and 51.7% versus 53.5% and 83.7%, respectively; p< 0.001); however, there was no significant improvement in DWI or ADC image quality, or DWI degree of distortion or artefact. There was a trend towards a lower number of corrupted data points from the contrast curve (2.47±2.44 versus 3.68±2.64), but this did not reach significance ( p= 0.052). Conclusion: Administration of HBB significantly improves the image quality of T2WI images. These results provide evidence for the use of HBB in routine patient preparation prior to prostate mpMRI. Highlights: HBB administration significantly improved the quality of anatomical T2W images. HBB administration significantly reduced motion artefact and blurring on T2W images. Differences in DW and DCE image quality post-HBB were not statistically significant. DWI may be less affected due to its short EPI-readout acquisition time. Using HBB in patient preparation prior to prostate MRI is recommended.